Efektivitas Model Project Based Learning Pada Mata Pelajaran Instalasi Motor Listrik Kelas XI TITL SMK Negeri 1 Batipuh - Dila Dea Roza; Usmeldi Usmeldi (Journal of Electrical Vocational Education, 2025)
This study aims to determine the effectiveness of the Project Based Learning model in the subject of electric motor installation for class XI TITL SMK Negeri 1 Batipuh. This type of research is quantitative research with the type of Quansi Experimental research with the design of Pretest-Posttest Nonequivalent Control Group Design. The design or plan of this study consists of experimental and control groups. This research was conducted in class XI TITL with 23 respondents. To measure this effectiveness, a pretest was given before the application of the project based learning model in learning, the posttest was given after the learning process of electric motor installation. The results of the posttest will be analyzed using a series of tests such as analysis of the completeness of learning outcomes, effect size. The test results showed that 20 students obtained scores above the KKTP / Complete with a percentage of 87%, while 3 other students obtained scores below the KKTP / not complete. Thus, the analysis of student learning completion after learning with the project based learning model was said to be effective and the effect size test showed that learning with the project Based Learning model was effective in improving student learning outcomes.